DESKRIPSI PENGETAHUAN DAN PENERAPAN TANAMAN OBAT KELUARGA (TOGA) DI DESA PINILIH KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Cristian Hendri Mewengkang; Elsje Pauline Manginsela; Melsje Yellie Memah (Sam Ratulangi University, 2020)
This study aims to describe the knowledge and application of this knowledge about the types of Family Medicinal Plants (TOGA). Research location in Pinilih Village, Dimembe Sub-district, North Minahasa Regency. The data used in this study are primary and secondary data. The sampleselection is done intentionally, namely the community members who plant medicinal plants in their homeyard. Primary data collection conducted by direct interviews with 20 community members withthe help of a list of questions. Secondary data were obtained from the Pinilih Village Office, University Library, and the Internet. The method of analysis used in this research is descriptive analysis. The results showed that respondents had knowledge of the types of medicinal plants and knew their benefits. There were those who know the uses of medicinal plants without using or applying them and there were also not only knowing but also applying their knowledge. Knowledge about types of medicinal plants and their benefits and how to use them is applied in family life because it is a legacy from the family therefore that has been used for a long time and is still used until today. The types of medicinalplants of this family are not only planted in the yard but also in the garden.*eprm*